STUDI PERBANDINGAN HASIL PEMINDANGAN IKAN LAYANG (Decapterus ruselli Rupel) DI UD. SAMUDERA EXECUTIVE DAN UD. BAROKAH DI DESA SUMBERANYAR KECAMATAN BANYUPUTIH KABUPATEN SITUBONDO - Ismi Jasila; Ika Junianingsih (Faculty of Science and Technology University Ibrahimy, 2015)
The purpose of this study was to determine differences pemindangan process as well as the results obtained from the way pemindangan held at UD. Samudera Executive and UD. Barokah. The method used in this research is the survey method. The primary data obtained directly by means of observation, interviews with the competent authorities in the field. While secondary data obtained from the study of literature associated with the study material. The results showed that there are differences in the treatment of fish pemindangan process conducted at UD. Samudera Executive to that done at UD. Barokah. At UD. Executive Ocean, the addition of salt to 1 ton of fish as much as 3 quintals on salting stage, 50 kg in the preparation stage and 50 kg in the boiling phase. While at UD. Barokah addition of salt as much as 2 quintals in 1 ton of fish for all treatments. Thus, the results of boiled fish at UD. Executive Ocean fish texture denser and drier and the fish looks intact and not broken. It can be concluded that the difference in the amount of salt can affect the quality of boiled fish